2006
DOI: 10.1002/cncr.21708
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery followed by intraperitoneal hyperthermic perfusion

Abstract: BACKGROUNDThe purpose of this prospective Phase II study was to analyze morbidity and mortality of cytoreductive surgery (CRS) and intraperitoneal hyperthermic perfusion (IPHP) in the treatment of peritoneal surface malignancies.METHODSA total of 205 patients (50 with peritoneal mesothelioma, 49 with pseudomyxoma peritonei, 41 with ovarian cancer, 32 with abdominal sarcomatosis, 13 with colon cancer, 12 with gastric cancer, and 8 with carcinomatosis from other origins) underwent 209 consecutive procedures. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(67 citation statements)
references
References 34 publications
4
60
0
3
Order By: Relevance
“…In our study we found 29 postoperative infections in 30 patients, with a 36% rate of infected patients (11/30), and 2.6 infections per patient. This rate is in the range of those reported in the literature (3.3-62.5%) [11,[24][25][26]. However, most of these studies were designed to assess the overall complications of peritonectomy, and not to address postoperative infections specifically.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our study we found 29 postoperative infections in 30 patients, with a 36% rate of infected patients (11/30), and 2.6 infections per patient. This rate is in the range of those reported in the literature (3.3-62.5%) [11,[24][25][26]. However, most of these studies were designed to assess the overall complications of peritonectomy, and not to address postoperative infections specifically.…”
Section: Discussionmentioning
confidence: 76%
“…In these trials [11,26], infectious complications, especially sepsis and septic shock, were the cause of half deaths. Kusamura [24]. In a more recent study, Sugarbaker et al [25] found 42 % of infectious complications in grade III (National Cancer Institute's Common Toxicity Criteria) (http:// ctep.cancer.gov), adverse events, including 17% line sepsis, 17% urinary tract infections, 5% wound infections, and 3% abdominal abscesses; moreover, they found a 5% infection rate in procedures complicated by grade IV adverse event.…”
Section: Discussionmentioning
confidence: 97%
“…After the gastrointestinal tract, the respiratory tract is probably the system that is most affected by postoperative complications. Pulmonary morbidity was found in six cases of our series and the majority of these were resolved without reintervention or invasive procedures, with the exception of a case of pulmonary embolism [25]. …”
Section: Discussionmentioning
confidence: 99%
“…High rates of potential fatal complications associated with HIPEC have been reported in the literature [1, 2]; that is why some patients need to be admitted to intensive care unit for stabilization, detection, and early resolution of complications associated with the extension of the surgical procedure, the toxicity of the drugs administered, or both. Particular emphasis should be placed on the dose of cisplatin administered i.p., because in a multivariate analysis it has been reported that doses >240 mg correlate with the appearance of postoperative complications [35]. Post-HIPEC morbidity rates range from 30 to 74% and mortality ranges from 0 to 19% [1, 2, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Śmiertelność wyniosła 0,9%. W analizie wieloczynnikowej niezależny-mi czynnikami ryzyka zwiększonej częstości występo-wania powikłań była rozległość cytoredukcji oraz dawka cisplatyny [40]. W ostatnim przeglądzie systematycznym dotyczącym bezpieczeństwa zabiegu CRS i HIPEC stwierdzono, że chorobowość i śmiertelność zabiegu jest podobna jak w przypadku dużych zabiegów chirurgicznych, takich jak operacja Whippla.…”
Section: Omówienieunclassified